PENGGUNAAN PREZI UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT MEDIA PEMBELAJARAN - Totalia, Salman Alfarisy; Martono, Trisno; Baedhowi, Baedhowi; Sawiji, Hery; Wahyono, Budi (Jurnal Pendidikan Insan Mandiri, 2016)
?SMP Terbuka? or Open Junior High School is an formal education that applying the concept of independent study which is allocated for school age children who had undergone resistance that make them was not possible to follow education in Regular Junior High School. The learning process in Open Junior High School was totally different with Reguler Junior High School since the condition of almost students in Open School have worked to help their parents. However, standard competence graduates (SKL) and curriculum in Open Junior High School was same as in Reguler Junior High School. The other problem is Lack of ability teachers in Open Junior High School in making an learning media that interesting. This study is purposes to improve the ability of teachers in SMP Terbuka Kemusu and SMP Terbuka Wonosegoro in making an learning media with Prezi software. The result of this study showed that been increasing in the ability of teachers in SMP Terbuka Kemusu and SMP Terbuka Wonosegoro in making an learning media with Prezi. The improvement in the ability of teachers in making an learning media with Prezi was beyond the target scores.Keywords: Open Junior High School, Learning Media, Prezi